10 Jahre Berliner Künstlerprogramm. (Berlin : DAAD - Berliner Künstlerprogramm Berlin, 1975)
AAkrithakis, Alexis ; Albanese, Russero ; Arakawa, Shusaku ; Armitage, Kenneth ; Arroyo, Eduardo ; Attersee, Christian-Ludwig ; Baker, George ; Balint, Endre ; Baratella, Paola ; BehrmannAngelika ; Benrath, Frédéric, Bertholo, René ; Black, David ; Bokor, MiklosBoltanski, Christian ; Brisley, Stuart ; Broodthaers, Marcel ; Brouwn, Stanley ; Brusse, Mark ; Buren, Daniel ; Byars, James Lee ; Calzolari, Pier Paolo ; Caniaris, Vlassis ; Canogar, Rafael ; Castillo, Jorge ; Christmann, Gunter S. ; Colville, Alex ; Cook, W. Delafield ; etc.
10 Jahre Berliner Künstlerprogramm, DAAD, Berlin, 1975
boek